Developing Techniques for Quantitative Renal Magnetic Resonance Imaging - Daniel, Alexander James (2021)
The kidneys are morphologically and functionally complex organs and as such, lend themselves to complex methodologies of study. One such methodology is quantitative Magnetic Resonance Imaging (MRI). Rather than simply taking a structural image of the kidneys, quantitative MRI aims to measure physical properties such as the rate of blood flow, tissue perfusion, oxygen consumption and more fundamental properties of the matter making up the organ such as its proton density or longitudinal relaxation time, T1 and transverse relaxation time T2. This is done without the need for ionising radiation and often without exogenous contrast agents, thus making MRI an ideal tool for both clinical and research use. Multiple methods have been developed to measure the transverse relaxation time, T2, of the kidneys, often leading to inconsistent results between studies. Here, a methodical comparison of four prominent techniques is performed. This comparison makes use of quantitative phantoms before proceeding to assess each technique in-vivo in healthy volunteers. A Gradient Spin Echo (GraSE) sequence is recommended for future renal T2 mapping.